103k views
1 vote
Write a equivalent equation for y-6=-12(x+4)​

1 Answer

3 votes

For this case we must find an equation equivalent to:


y-6 = -12 (x + 4)

We apply distributive property to the terms within parentheses taking into account that:


- * + = -

So:


y-6 = -12x-48

We add 6 to both sides of the equation:


y = -12x-48 + 6

We add similar terms taking into account that different signs are subtracted and the sign of the major is placed:


y = -12x-42

Thus, an equivalent equation is:
y = -12x-42

ANswer:


y = -12x-42

User TimHayes
by
6.3k points